Key factors in designing self-excited renewable energy system - Nik Fazli Sapian; Khairul Azhar Mat Daud; Ahmad Rasdan Ismail (Universiti Malaysia Kelantan, 2015)
For many people, powering their homes or small businesses using a small renewable energy system that is not connected to the electricity grid – is called a self-excited system. In remote locations, self-excited systems can be more cost-effective than extend- ing a power line to the electricity grid, but these systems are also used by people who live near the grid and wish to obtain independ- ence from the power provider or demonstrate a commitment to non-polluting energy sources. Thus, this paper focuses on key factor sof using self-excited renewable energy system namely cost effective, environmental friendly and independent from power sources. Existing research is highlighted and reviewed based on its findings.